B cell subsets reconstitution and immunoglobulin levels in children and adolescents with B non-Hodgkin lymphoma after treatment with single anti CD20 agent dose included in chemotherapeutic protocols: single center experience and review of the literature - Hlaváčková, Eva; Křenová, Zdenka; Kerekes, Árpád; Slanina, Peter; Vlková, Marcela (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
BACKGROUND: RTX, an anti-CD20 monoclonal antibody, added to chemotherapy has proven to be effective in children and adolescents with high-grade, high-risk and matured non-Hodgkin lymphoma. RTX leads to prompt CD19+ B lymphocyte depletion. However, despite preserved immunoglobulin production by long-lived plasmablasts after treatment, patients remain at risk of prolonged hypogammaglobulinemia. Further, there are few general guidelines for immunology laboratories and clinical feature monitoring after B cell-targeted therapies. The aim of this paper is to describe B cell reconstitution and immunoglobulin levels after pediatric B-NHL protocols, that included a single RTX dose and to review the literature. METHODS: A retrospective single-center study on the impact of a single RTX dose included in a chemotherapeutic pediatric B Non-Hodgkin Lymphoma (B-NHL) treatment protocols. Immunology laboratory and clinical features were evaluated over an eight hundred days follow-up (FU) period, after completing B-NHL treatment. RESULTS: Nineteen patients (fifteen Burkitt lymphoma, three Diffuse large B cell lymphoma, and one Marginal zone B cell lymphoma) fulfilled the inclusion criteria. Initiation of B cell subset reconstitution occurred a median of three months after B-NHL treatment. Naïve and transitional B cells declined over the FU in contrast to the marginal zone and the switched memory B cell increase. The percentage of patients with IgG, IgA, and IgM hypogammaglobulinemia declined consistently over the FU. Prolonged IgG hypogammaglobulinemia was detectable in 9%, IgM in 13%, and IgA in 25%. All revaccinated patients responded to protein-based vaccines by specific IgG antibody production increase. Following antibiotic prophylaxes, none of the patients with hypogammaglobulinemia manifested with either a severe or opportunistic infection course. CONCLUSION: The addition of a single RTX dose to the chemotherapeutic treatment protocols was not shown to increase the risk of developing secondary antibody deficiency in B-NHL pediatric patients. Observed prolonged hypogammaglobulinemia remained clinically silent. However interdisciplinary agreement on regular long-term immunology FU after anti-CD20 agent treatment is required.
Keywords: Immunoglobulins; Retrospective Studies; protokoly antitumorózní kombinované chemoterapie; mladiství; B-Lymphocyte Subsets; mužské pohlaví; podskupiny B-lymfocytů; dítě; Child; Child, Preschool; Rituximab; ženské pohlaví; retrospektivní studie; předškolní dítě; Humans; B-buněčný lymfom; rituximab; Antineoplastic Combined Chemotherapy Protocols; imunoglobuliny; nehodgkinský lymfom; Lymphoma, B-Cell; Lymphoma, Non-Hodgkin; protinádorové látky imunologicky aktivní; Female; Adolescent; Antineoplastic Agents, Immunological; lidé; Male